Aggregation/dispersion-mediated peroxidase-like activity of MoS2 quantum dots for colorimetric pyrophosphate detection. Issue 14 (28th January 2019) - Xia, Wanqiang; Zhang, Pu; Fu, Wensheng; Hu, Lianzhe; Wang, Yi
Abstract : Peroxidase-like activity of MoS2 quantum dots can be manipulated by aggregation/dispersion in the presence of Fe 3+ or a mix of Fe 3+ and pyrophosphate (PPi). Based on this finding, a simple and reliable method for colorimetric PPi detection is developed. Abstract : Peroxidase-like activity of MoS2 quantum dots can be manipulated by aggregation/dispersion in the presence of Fe 3+ or a mix of Fe 3+ and pyrophosphate (PPi). Based on this finding, a simple and reliable method for colorimetric PPi detection is developed.